Situation Report: Romania, 24 July 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Jordanian Crown Prince Visits Bucharest Economy Begins to Return to Normal after Floods Decree on Price Increases Published Law Review Discusses Combined Party-State Bodies Historical Unity of Romanian People Emphasized